A patrimonialização da memória social: uma forma de domesticação política das memórias dissidentes ou indígenas? - Alejandra Aguilar Pinto (Ciências Sociais Unisinos)
This article aims to introduce memorization practices, experienced by diverse groups, focusing on hegemonic memories (such as those represented in memory institutions like museums and archives as well as those carried on by its professional archivists, librarians, historians and official state policies of patrimonialization) and dissenting memories (in our case, indigenous thought). The definition of history and memory (Popular memory group, 1982) has played a key-role during the construction of national identities and political domination, through the imposition of specific and partial versions as universal and shared ones, and through the occlusion, exclusion and silencing of the meanings of the past for subaltern groups. The same dynamic applied in processes of colonization, expropriation (Bonfil, 1993) and domestication (Gnecco, 2000). This paper questions to what extent the official mechanisms or devices of memory and forgetting were successful in silencing, change or represent truly the "non-hegemonic voices". On the other side, the paper introduces "new" forms of inscription and expression of non-hegemonic memories, other than documents in archives, such as body (corporal painting), rituals and landscape (sacred lands). Therefore, the definition of historical text expands dramatically. This research is situated at the crossroad of global and local cultural practices, which are represented most obviously in challenges around the definition of identities. Systems of historical representation (such as archives and museums) have played a crucial role in meeting this challenge. In spite of relations of subordination experienced by indigenous people, some groups have had success in reinventing and construct "another history".